The Decision Support System in Selecting The Characteristics of Coffee By Using Analytic Hierarcy Process Method - Novrini Hasti; Riswan Fitriyandi (Universitas Multimedia Nusantara, 2019)
This study is to determine whether the characteristics of coffee flavor can be implemented into a decision support system. In this study, the problem is the difficulty in finding coffee experts with adequate understanding and knowledge of coffee. The purpose is to implement Analytic Hierarchy Process (AHP) method to determine the characteristics of coffee flavor and to transfer the knowledge about the taste of coffee to coffee lovers. The expected results are to assist in making a decision support system application in selecting the characteristics of coffee, so that it can provide the advice to the common consumers who want to enjoy and the knowledge about the coffee itself as well.